Validity of evaluation instrument on the implementation of performance assessment to measure science process skills - Ramadani, Marina; Supahar, Supahar; Rosana, Dadan (Jurnal Inovasi Pendidikan IPA, 2017)
This study aims to develop an evaluation instrument CIPP (context, input, process, product) model that suitable at implementation of performance assessment instrument to measure students' science process skills of junior high school. Methods in this study are research and development (R & D) which is adopted by model Borg & Gall model. This evaluation instrument used one of evaluation CIPP model with context, input, process, and product components. The evaluation instrument is used to determine the implementation of performance assessment instrument to measure junior high school students' science process skills in excretion system topic. This development study involves some experts to give validation of the development of feasibility products. Experts involved, they are two lecturers of evaluation expert, two junior high school science teachers, and four peers. The validity of evaluation instruments was analyzed using V'aiken formula. The results of this study are evaluation instrument of CIPP model of the implementation of performance assessment to measure junior high school students' science process skills of grade VIII in excretion system topic. The results of the validity of this product indicates that this evaluation instruments are eligible in using with V'eiken coefficient of 0.86. It indicates that the evaluation instruments are valid in substance, construction, and language aspects.